Vitamin D alleviates non-alcoholic fatty liver disease via restoring gut microbiota and metabolism - Zhang, Xiao-Lei; Chen, Lei; Yang, Jiang; Zhao, Shan-Shan; Jin, Shi; Ao, Na; Yang, Jing; Liu, Hui-Xin; Du, Jian (Frontiers in Microbiology, 2023)
Background Non-alcoholic fatty liver disease (NAFLD) represents a severe public health problem. Dysbiosis of gut microbiome has been identified as one of the key environmental factors contributing to NAFLD. As an essential nutrition, Vitamin D (VD) plays an important role in regulating gut microbiota based on its receptor (Vitamin D Receptor, VDR) which is highly expressed in the gastrointestinal tract. Methods Rats were fed with HFD (high-fat diet) for 12 weeks. And the rats were treated with VD two times a week by intraperitoneal injection for 12 weeks. H&E staining combined with plasma biochemical index was performed to characterize pathological changes and function of the liver. Fecal microbiota 16S rRNA gene sequencing and metabolomics were taken to reveal the altered gut microbiota and metabolites. Result The VD alleviates the HFD-induced lipid accumulation in the liver as well as decreases the levels of amlodipine besylate (ALT) and amlodipine aspartate (AST). VD supplement decreased the ratio of phylum Firmicutes/Bacteroidetes (F/B) but increased alpha diversity. In addition, the VD treatment improved the HFD-induced gut microbiota by increasing the Prevotella and Porphyromonadaceae and decreasing Mucispirillum, Acetatifactor, Desulfovibrio, and Oscillospira abundance. Furthermore, the capability of tyrosine metabolism, tryptophan metabolism, arginine biosynthesis, and sphingolipid metabolism was enhanced after VD treatment. Consistently, Prevotella positively correlated with tryptophan metabolism and sphingolipid metabolism. Importantly, the Prevotella abundance was positively associated with serotonin, melatonin, tryptamine, L-arginine, and 3-dehydrosphinganine which synthesize from tryptophan, tyrosine, arginosuccinate, and serine, respectively. Conclusion VD treatment inhibited HFD-induced NAFLD accompany by dysbiosis gut microbiota and metabolites, suggesting that VD supplement could be a potential intervention used for NAFLD treatment by targeting the specific microbiota.